2014
DOI: 10.1177/1468017314549690
|View full text |Cite
|
Sign up to set email alerts
|

Family quality of life and child psychological well-being in Palestine: A pilot case study

Abstract: Bringing to bear an ecological perspective on functioning and well-being, the present work investigated the relationship between impact of trauma in children living in war-like conditions and their parents' quality of life (QoL). Seventy-four schoolaged children completed self-report measures assessing their personal life satisfaction and perceptions of parental support. Fifty-three parents completed self-report measures assessing their own quality of life.Findings: Although these Palestinian children presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 85 publications
(133 reference statements)
2
16
0
Order By: Relevance
“…With regard to the outcomes of being exposed to traumatic events, the data confirmed the moderate levels of traumatization in helpers already identified in previous studies with different samples of health professionals working in Palestinian refugee camps (Veronese, Fiore, Castiglioni, & Natour, 2014; Veronese & Pepe, 2013, 2014).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…With regard to the outcomes of being exposed to traumatic events, the data confirmed the moderate levels of traumatization in helpers already identified in previous studies with different samples of health professionals working in Palestinian refugee camps (Veronese, Fiore, Castiglioni, & Natour, 2014; Veronese & Pepe, 2013, 2014).…”
Section: Resultssupporting
confidence: 84%
“…We found that levels of trauma were directly and negatively correlated to subjective well-being (H1). The more Palestinian practitioners are exposed to violent trauma, the more their psychological well-being is at risk of being undermined (Karamouzian & Carmichael, 2014; Veronese et al., 2014). This finding is confirmed by previous studies documenting the extreme sense of insecurity and threat that Palestinian helpers have to cope with, due to the ongoing military occupation and its consequences for the health system in the OPT (Giacaman et al., 2009; Veronese, 2013; Veronese et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite several studies linking parental incarceration to adverse outcomes, children with incarcerated parents have also been shown to be resilient in the face of adversity. Extended family support of children with incarcerated parents has been associated with positive developmental and psychological outcomes ( Miller, 2007 ), just as a supportive family environment is associated with resilience in other populations facing adversity (e.g., Masten, 2011 ; Veronese and Castiglioni, 2013 ; Veronese et al, 2014 ). In addition, children with incarcerated parents who have positive relationships with their caregivers and incarcerated parents may have better behavioral outcomes ( Dallaire, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…When families affected by armed conflict are asked to speak about their quality of life (QoL), education is mainly referred to as a key dimension affecting the well-being of the younger generations (Bragin & Opiro, 2012;Veronese, Castiglioni, Barola, & Said, 2012;Veronese, Castiglioni, Tombolani, & Said, 2012;Veronese & Castiglioni, 2013;Veronese, Fiore, Castiglioni, & Natour, 2014). In fact, the community frequently views education as a means of providing hope and a better future for the youth.…”
Section: Introductionmentioning
confidence: 99%